2020
DOI: 10.1029/2020gl089192
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Timpson Induced Earthquake Sequence: A System of Two Parallel Faults

Abstract: The 17 May 2012 M4.8 Timpson earthquake is the largest known earthquake in eastern Texas. It is thought to have been induced by wastewater injection from two nearby, high‐volume wells. Its cataloged aftershocks form a NW‐SE trend, which unlike other induced earthquakes sequences is unfavorably oriented for failure in the local stress field. To understand this, we enriched the catalog using PhaseNet, a deep‐learning‐based picker followed by double‐difference relocation with cross‐correlation‐based differential … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…However, ruptures may span multiple nearby fault segments (e.g., Landers earthquake, Li et al., 1994; and Hector Mine earthquake, Treiman et al., 2002) such that the maximum fault length is not a reliable predictor of the maximum earthquake magnitude. Such co‐slipping of en‐echelon fault systems has been observed for induced seismicity in Alberta, Canada (M W 4.1, Wang et al., 2018) and east Texas (M 4.8, Wang, Ellsworth et al., 2020). Within the Raton Basin, the largest earthquake since the beginning of injection was the M W 5.3 Trinidad event with a geodetically estimated rupture length of ∼8–10 km (Barnhart et al., 2014), which is shorter than the ∼14 km total length of the Trinidad zone of seismicity (Meremonte et al., 2002; Rubinstein et al., 2014).…”
Section: Discussionmentioning
confidence: 75%
“…However, ruptures may span multiple nearby fault segments (e.g., Landers earthquake, Li et al., 1994; and Hector Mine earthquake, Treiman et al., 2002) such that the maximum fault length is not a reliable predictor of the maximum earthquake magnitude. Such co‐slipping of en‐echelon fault systems has been observed for induced seismicity in Alberta, Canada (M W 4.1, Wang et al., 2018) and east Texas (M 4.8, Wang, Ellsworth et al., 2020). Within the Raton Basin, the largest earthquake since the beginning of injection was the M W 5.3 Trinidad event with a geodetically estimated rupture length of ∼8–10 km (Barnhart et al., 2014), which is shorter than the ∼14 km total length of the Trinidad zone of seismicity (Meremonte et al., 2002; Rubinstein et al., 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Although the rate has declined since 2015, there were still 130 M3+ earthquakes recorded in the same region in 2019. Some of them were particularly strong and damaging such as the M5.8 Pawnee and M5.0 Cushing Oklahoma earthquakes that occurred in 2016 [15][16][17].…”
Section: Timementioning
confidence: 99%
“…Although earthquakes can be induced in many ways such as the filling up subsurface reservoirs, oil and gas production, fluid injection, mining, geothermal energy extraction, and other operations, each of these activities fundamentally causes earthquakes due to the same mechanism: a sudden release of stored elastic strain energy by frictional sliding along preexisting faults due to the change of their stress conditions [14]. Observations and numerical modeling showed that increased fluid pressure within faults is the main risk factor whether injection well will trigger earthquakes [12][13][14][15][16][17][18]. A case history of injectioninduced seismicity demonstrated that elevating the pore pressure by hundreds of psi could cause a previously quiescent area to become seismically active when the regions are sufficiently prestressed [13,38].…”
Section: Mechanisms Of Injection-caused Seismicitymentioning
confidence: 99%
“…In the seismology community, there have been several recent works studying the importance of the model generalization (Chai et al., 2020; Liu et al., 2020; Mousavi et al., 2020; Park et al., 2020; K. Wang, Ellsworth, & Beroza, 2020; R. Wang, Schmandt, et al., 2020). As demonstrated in most of these recent studies, DNN‐based models yield some generalization ability that would allow for a model being trained on one data set to then be applied to a different study region.…”
Section: Introductionmentioning
confidence: 99%
“…In the seismology community, there have been several recent works studying the importance of the model generalization (Chai et al, 2020;Liu et al, 2020;Mousavi et al, 2020;Park et al, 2020;K. Wang, Ellsworth, & Beroza, 2020; R. Wang, Schmandt, et al, 2020).…”
mentioning
confidence: 99%